Digital tools in the potato value chain in Kenya: A landscape analysis - Borus, Dinah (International Food Policy Research Institute, 2023)
Potato sector has a substantial role in Kenya's agriculture, contributing to food security, nutrition, and the national economy. While underscoring the sector's vast potential, this Technical Brief identifies the existing gap between current yields and achievable targets, highlighting the necessity for strategic improvements in farming practices. It accentuates the transformative impact of digital tools in the agricultural landscape, notably accelerated by the COVID-19 pandemic and facilitated by the widespread use of mobile technology and internet access in the country. In particular, this brief spotlights the Viazi Soko (VS) digital platform, an initiative specifically designed for the potato value chain, offering a range of services from e-advisory to market linkages. Despite the innovative features and strategic importance of digital platforms, the underlying research reveals a discrepancy in the adoption and utilization of digital tools among farmers, attributed to challenges such as limited awareness of these tools, low internet connectivity in rural areas, and the affordability of digital access. To bridge this digital divide, the report proposes targeted interventions to enhance the adoption of digital tools, focusing on increasing awareness, improving digital literacy, and establishing a potato-specific call center to provide real-time, tailored support to farmers. By advocating for a more integrated approach that combines digital innovation with farmer education and support, the report envisions a future where digital tools are leveraged to unlock the full potential of the potato sector in Kenya, leading to increased productivity, profitability, and a more robust contribution to the nation's food security and economic resilience.